2012
DOI: 10.1016/j.celrep.2012.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of the Cholesterol Exporter ABCA1 Gene

Abstract: Summary The ABCA1 protein mediates the transfer of cellular cholesterol across the plasma membrane to apolipoprotein A-I. Loss-of-function mutations in the ABCA1 gene induce Tangier disease and familial hypoalphalipoproteinemia, both cardio-vascular conditions characterized by abnormally low levels of serum cholesterol, increased cholesterol in macrophages and subsequent formation of vascular plaque. Increased intra-cellular cholesterol levels are also frequently found in cancer cells. Here we demonstrate anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(171 citation statements)
references
References 84 publications
8
148
1
Order By: Relevance
“…ABCA1 has been found to play a crucial role in the etiology of various neurological and cardiovascular diseases, including inflammation and metabolic syndrome (21), and may also be involved in the initiation and development of prostate cancer. A causal association between ABCA1-mediated tumor inhibition and mitochondrial cholesterol depletion has been identified through testing the dependence of ABCA1 anticancer activity on its efflux capacity (22). In addition, transforming growth factor (TGF)-β signaling plays a key role in prostate cancer occurrence and maintenance of cancer stem cell characteristics.…”
Section: Effect Of Abca1 On the Progression Of Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…ABCA1 has been found to play a crucial role in the etiology of various neurological and cardiovascular diseases, including inflammation and metabolic syndrome (21), and may also be involved in the initiation and development of prostate cancer. A causal association between ABCA1-mediated tumor inhibition and mitochondrial cholesterol depletion has been identified through testing the dependence of ABCA1 anticancer activity on its efflux capacity (22). In addition, transforming growth factor (TGF)-β signaling plays a key role in prostate cancer occurrence and maintenance of cancer stem cell characteristics.…”
Section: Effect Of Abca1 On the Progression Of Prostate Cancermentioning
confidence: 99%
“…The antitumor effects of these compounds may involve a variety of mechanisms: Statins inhibit GTPases such as Ras and Rho family proteins via blocking protein prenylation and/or farnesylation, and LXR agonists induce cell cycle arrest through upregulation of p27. Conversely, intracellular cholesterol promotes prostate cancer progression as a substrate for de novo androgen synthesis and through regulation of Akt signaling (22).…”
Section: Effect Of Abca1 On the Progression Of Prostate Cancermentioning
confidence: 99%
“…Although ABCA1 was previously found to decrease cell proliferation, its relationship with metastasis is still unknown (38). To determine whether ABCA1-regulated cholesterol levels control metastatic capacity, we used an RNAi strategy and knocked down ABCA1 in MDA-MB-231 cells ( Supplementary Fig.…”
Section: The Cholesterol Efflux Channel Abca1 Drives Metastasis In Humentioning
confidence: 99%
“…Accumulating lines of evidence suggest that cholesterol homeostasis and biosynthesis usually appear to be altered in cancer cells and, once inhibited, the tumor genesis can be blocked indicating that cholesterol content tightly regulates cancer cell fate [13,14]. Recent studies have reported that constitutive activation of PI3K/Akt signaling pathway induces an increase in intracellular cholesterol content in cancer cells through multiple mechanisms, including induction of LDL receptor-related cholesterol import, activation of sterol regulatory element binding protein (SREBP)-dependent cholesterol synthesis and inhibition of ATP-binding cassette transporter ABCA1-regulated mTORC1-dependent cholesterol export [8,[15][16][17]. Further studies reveal that the increase of cholesterol levels is responsible to cancer cell growth, cell survival and cancer aggressiveness and bone metastases [15,16,[18][19][20][21].…”
Section: Deregulation Of Cellular Cholesterol Homeostasis By Cell Surmentioning
confidence: 99%
“…In recent decades, increasing lines of evidence show that lipid rafts, which are membrane micro domains assemble glycosphingolipids, protein receptors and kinases, preferentially associate with cholesterol and saturated lipids in driving a wide variety of cellular signaling pathways [5,6]. Not only in normal cellular and physiological functions, intracellular cholesterol homoeostasis once deregulated can be responsible for the development of malignancies through decreasing chemotherapeutic susceptibility and increasing resistance in cancer cells, inhibiting the release of mitochondrial cell death-promoting molecules, activating survival kinases and many other mechanisms [7][8][9]. Epidemiological studies also have suggested a positive correlation between serum cholesterol levels and cancer risk [9][10][11].…”
Section: Introductionmentioning
confidence: 99%